2016
DOI: 10.1089/jir.2015.0067
|View full text |Cite
|
Sign up to set email alerts
|

HMGB1 Turns Renal Tubular Epithelial Cells into Inflammatory Promoters by Interacting with TLR4 During Sepsis

Abstract: Our study was undertaken to investigate whether the inflammatory mediator high-mobility group box 1 (HMGB1) can enter the renal tissue and urine and what is the functional change of renal tubular epithelial cells (TECs) interacting with HMGB1 during sepsis. We found that the transcription levels of interleukin 1 (IL-1) and interleukin 6 (IL-6) mRNA in TECs increased significantly during sepsis and these processes can be blocked by splenectomy. We also found out HMGB1 accumulated in the renal tissue and entered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 36 publications
2
18
0
Order By: Relevance
“…However, to date, little progress has been achieved and the mechanisms inducing AKI during sepsis are still mysterious. In our previous study that aimed to look for the possible mechanisms of SAKI, we found out that the alteration of functional status and structure of TECs was critically related to the occurrence of SAKI [34,35]. These findings are consistent with the conclusions of previous studies focusing on AKI.…”
Section: Discussionsupporting
confidence: 89%
“…However, to date, little progress has been achieved and the mechanisms inducing AKI during sepsis are still mysterious. In our previous study that aimed to look for the possible mechanisms of SAKI, we found out that the alteration of functional status and structure of TECs was critically related to the occurrence of SAKI [34,35]. These findings are consistent with the conclusions of previous studies focusing on AKI.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, HMGB1 accumulates in the renal tissue and can enter the urine. Moreover, the interaction between HMGB1 and TLR-4 converts tubular epithelial cells into inflammatory promoters during sepsis (27). In this study, we confirmed that both typical receptors (i.e., receptor for advanced glycation end product, TLR-2, and TLR-4), and inflammatory cytokines were considerably elevated in CLP mice, further supporting the role of HMGB1-mediated inflammation in sepsis.…”
Section: Discussionsupporting
confidence: 79%
“…Duan et al (20) evaluated the HMGB1 levels in the serum of 60 patients with HBV-related ACLF, 30 with chronic hepatitis B and 24 healthy kin-1 and, also, IL-6 (31) . Likewise, HMGB1 can accumulate in the renal tissue and urine, stimulating the production of inflammatory cytokines, including IL-6, through interaction with toll-like receptors 4 (32) . Elevated levels of toll-like receptors 4 are found in the renal tubular cells of cirrhotic patients with AKI, suggesting that these receptors may mediate renal injury in the context of infection or systemic inflammation (33) .…”
Section: Discussionmentioning
confidence: 99%